Evaluasi Implementasi Standar Operasional Prosedur Berbasis Community-Based Tourism dalam Meningkatkan Kualitas Pelayanan Pengunjungdi Desa Wisata Lebak Muncang - Zia Kemala; Kurnia Abdul Rasid (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2026)
Community-based tourism village development requires consistent and high-quality service standards to enhance visitor satisfaction and ensure destination sustainability. Desa Wisata Lebak Muncang is one of the tourism villages experiencing an increase in visitor numbers, thus requiring a standardized service system. This study aims to analyze the implementation of Standard Operating Procedures (SOP) in visitor services and to evaluate the gap between established standards and actual practices in the field. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation studies. Data analysis is conducted using the interactive model of Miles and Huberman, as well as the Service Quality (SERVQUAL) approach, which consists of five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results indicate that SOP implementation has covered aspects such as homestay services, tour guiding, security, and service coordination. However, the implementation has not been optimal due to significant gaps between standards and practice, particularly in the dimensions of reliability and responsiveness. The main challenges include low levels of SOP compliance, limited human resource competencies, and suboptimal evaluation and monitoring systems. This study contributes by proposing a Community-Based Tourism (CBT)-based SOP strengthening model that emphasizes community capacity building, strengthened monitoring systems, and the integration of local values into service standards.